Violent planet - Steele, Philip, 1948-; Barber, Nicola; Morris, Neil. (Tunbridge Wells, Kent [England] : ticktock Media, 2008)
Examines natural disasters, which includes volcanic eruptions, earthquakes, fires, tornadoes, hurricanes, and tsunamis; and discusses which countries are at risk, how scientists monitor danger areas, and preventative actions.
Includes index.
5.8
3-6
Keywords: Natural disasters -- Juvenile literature; Natural disasters; Natural disasters